Assessment of Nitrogen Content in Buffalo Manure and Land Application Costs - Faugno, Salvatore; Pindozzi, Stefania; Okello, Collins; Ripa, Maria Nicolina (Journal of Agricultural Engineering, 2012)
Buffalo (Bubalus bubalis) livestock for mozzarella cheese production plays a fundamental role in the economy of southern Italy. European and Italian regulations consider nitrogen content in buffalo manure to be the same as that of cattle manure. This study aimed to assess whether this assumption is true. The first aim of the study was to assess nitrogen content in buffalo manure. Samples were taken from 35 farms to analyse nitrogen and phosphorous concentration in the manure. Analysis confirmed a lower nitrogen concentration (2%) in buffalo manure. A secondary aim of the study was to evaluate whether manure application techniques that are apparently less suitable, e.g. splash plate spreader, could be feasible. The cost of different methods of land application of manure and their characteristics were evaluated on the basis of one operational cycle. Considering losses for volatilisation, and taking into account cost assessment, the immediate incorporation of buffalo manure (nitrogen content 2%) is a suitable method of ammonia volatilisation. However, it is expensive and involves high fuel consumption in relation to the environmental benefit.